2009
DOI: 10.3233/jad-2009-1021
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: A Novel Therapeutic Strategy for Alzheimer's Disease

Abstract: Adipocyte-derived leptin appears to regulate a number of features defining Alzheimer's disease (AD) at the molecular and physiological level. One activity of leptin is the control of AMPdependent kinase (AMPK). In addition to maintaining lipid levels, AMPK regulates glycogen synthase kinase-3, which modulates tau phosphorylation. Leptin has been shown to reduce the amount of extracellular amyloid-β, both in cell culture and animal models of AD, as well as reduce tau phosphorylation in neuronal cells. Important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 94 publications
5
96
0
Order By: Relevance
“…3). In concert with other adipocytokines, such as leptin75, a complicated mode of APN may act as a driving force in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…3). In concert with other adipocytokines, such as leptin75, a complicated mode of APN may act as a driving force in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case-control study has measured the serum levels of adiponectin and leptin in the same cohorts of AD and confirmed a raised level of adiponectin and a lower leptin level in serum of AD subjects which are in good correlation with the severity of the disease as measured by MMSE scores [49]. Extensive experimental studies in cell lines and AD transgenic mice have indicated that leptin can affect APP-Aβ trafficking, Aβ accumulation and clearance, βsecretase expression as also phosphorylation of tau protein [139,140,147].…”
Section: Adipokinesmentioning
confidence: 99%
“…Improved memory following leptin administration has also been found in SAMP-8 mice, an accelerated senescence rodent model that develops amyloid plaques [37]. Chronic leptin administration to the APPoverexpressing mouse, Tg2576, by implanted miniosmotic pumps reduced brain amyloid levels significantly [44,47]. In a recent study by Doherty et al, it has been shown that leptin reverses the A inhibition of hippocampal LTP, reduces Ainduced facilitation of long-term depression (LTD) by PI3 kinase pathway, protects against A -induced internalization of glutamate receptor 1 subunit (GluR1) by PI3 kinasedependent mechanism thereby preventing removal ofamino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptors from the synapses in hippocampal neurons, protects cortical neuronal death against A -mediated toxicity by STAT3-mediated pathway, and reduces A -induced expression of synaptic protein endophilin 1 and phosphorylated tau in cortical neurons both in vitro and in vivo [50].…”
Section: Neuroprotective Functions Of Leptin In Experimental Modelsmentioning
confidence: 86%
“…Leptin prevents neuronal death by reducing A levels both in vitro and in vivo, as well as by reducing tau hyperphosphorylation [40,41]. The neuroprotective role of leptin has been extensively studied in both in vitro and in vivo models of neurodegeneration [42][43][44]. In vitro model of PD using cultured dopaminergic cells exposed to the neuronal toxin 6-hydroxydopamine (6-OHDA) has shown protection from death by leptin [39,42].…”
Section: Neuroprotective Functions Of Leptin In Experimental Modelsmentioning
confidence: 99%